Ablating Aspiration Needle Tract Prior to Microwave Ablation Can Improve Therapeutic Outcomes for Predominantly Cystic Thyroid Nodules - Yang, Haizhen; Chen, Yanwei; Chen, Baoding; Zhao, Shuangshuang; Zhang, Zheng; Wang, Keke; Chen, Zheming; Feng, Huahui; An, Maohui (Frontiers in Endocrinology, 2021)
Purpose: To investigate whether ablating aspiration needle tract could improve safety and efficacy of ultrasound-guided microwave ablation (MWA) for predominantly cystic thyroid nodules. Materials and methods: This retrospective study evaluated 41 predominantly cystic thyroid nodules that underwent MWA between June 2017 and August 2019. The nodules were stratiﬁed by different procedures into two groups: Aspiration needle tract was ablated before cyst fluid aspiration and MWA when treating 26 nodules in group A while the other 15 nodules in group B underwent MWA directly after cyst fluid aspiration. Baseline characteristics, intervention time, hospital stays, nodules with intraoperative intracystic hemorrhage and postoperative complications were compared between two groups. Volume, volume reduction rate (VRR), compressive score (CS) and aesthetic score (AS) were evaluated during follow-up. Results: Both groups achieved obvious decreases in volume, CS and AS, as well as an increase in VRR. Volumes and VRRs in group A at 1, 3, 6 and 12 months were significantly smaller and greater than that in group B (p＜0.001). The incidence of intraoperative intracystic hemorrhage in group A was significantly lower than that of group B (p=0.035). Compared to group B, hospital stays were much shorter in group A (p=0.040). There were no significant differences in intervention time, cystic fluid volume and postoperative complications. Conclusion: Aspiration needle tract ablation dramatically reduces the incidence of intraoperative intracystic hemorrhage and markedly improves the efficacy of MWA for predominantly cystic thyroid nodules.